Hawkins II and III Talus Neck Fractures: Complication Rates and Utility of Hawkins Sign - Logan Lake; Sarah Kurkowski MD; Augusto Roca BS; Henry Albert Kuechly BS; Andres Mor Huertas BS; Michael Thimmesch BS; Peter Spencer BS; Richard T. Laughlin MD (Foot & Ankle Orthopaedics)
Category: Trauma; Ankle Introduction/Purpose: Talus neck fractures typically result from hyperdorsiflexion in high-impact accidents like motor vehicle crashes and falls from significant heights. Complications arising from these fractures include avascular necrosis of the talus, sensory deficits, infection, and nonunion. Studies report varying rates of avascular necrosis for Hawkins II and III fractures, ranging from 20-35% and 40-70%, respectively. The Hawkins sign is a widely used diagnostic tool in clinical practice, employed around 6-8 weeks post-surgery to assess vascularity and predict the likelihood of complications. Our study aims to evaluate the reliability of the Hawkins sign and analyze rates of reoperation and avascular necrosis in patients with talus neck fractures. Methods: A retrospective study was conducted on patients who sustained Hawkins II or III fractures between 2018 and 2022 at a Level 1 trauma center. The study involved a comprehensive review of electronic medical records to ascertain injury presentation, surgical interventions, and outcomes/complications. Six-week postoperative ankle x-rays were examined by a fellowship-trained foot and ankle orthopaedic surgeon to determine the presence or absence of the Hawkins sign; cases lacking x-rays around the 6-week mark were excluded from the analysis. Patients with less than 1 year of follow-up were also excluded from the analysis of avascular necrosis. Statistical analysis was then employed to delineate differences between Hawkins II and III talar neck fractures concerning reoperation, complications (such as avascular necrosis, nonunion, and infection), and to investigate whether the Hawkins sign was associated with the subsequent development of avascular necrosis. Results: Thirty-eight patients presenting with either a Hawkins II (21/38) or Hawkins III (17/38) talar neck fracture were included in the study. Hawkins III fractures exhibited significantly higher rates of avascular necrosis, infection, and reoperation compared to Hawkins II fractures, while nonunion rates did not show significant differences (Table 1a). Notably, the presence of the Hawkins sign did not demonstrate correlation with the development of avascular necrosis at the one-year post-surgery mark (Table 1b). Conclusion: Hawkins III fractures exhibit poorer outcomes compared to Hawkins II fractures, particularly in terms of avascular necrosis, infection, and the necessity for reoperation. The incidence of avascular necrosis in Hawkins III talar neck fractures aligns closely with current literature, whereas our reported rates for avascular necrosis in Hawkins II fractures were notably lower. Of note, the presence of a Hawkins sign at the six-week post-surgery mark did not show any association with the development of avascular necrosis. This raises important questions regarding the utility of the Hawkins sign in predicting outcomes for these fracture patterns.